2010
DOI: 10.1016/j.dam.2010.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Improved induced matchings in sparse graphs

Abstract: a b s t r a c tAn induced matching in a graph G = (V , E) is a matching M such that (V , M) is an induced subgraph of G. Clearly, among two vertices with the same neighbourhood (called twins) at most one is matched in any induced matching, and if one of them is matched then there is another matching of the same size that matches the other vertex. Motivated by this, Kanj et al.[10] studied induced matchings in twinless graphs. They showed that any twinless planar graph contains an induced matching of size at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…We then show that this strategy helps in obtaining kernels on weakly closed graphs for Capacitated Vertex Cover, Connected Vertex Cover, and Induced Matching all parameterized by the natural parameter solution size k. For these problems, polynomial kernels in degenerate graphs were known [5,6,12,18]. Our results thus extend the class of graphs for which polynomial kernels are known for these problems.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…We then show that this strategy helps in obtaining kernels on weakly closed graphs for Capacitated Vertex Cover, Connected Vertex Cover, and Induced Matching all parameterized by the natural parameter solution size k. For these problems, polynomial kernels in degenerate graphs were known [5,6,12,18]. Our results thus extend the class of graphs for which polynomial kernels are known for these problems.…”
Section: Introductionmentioning
confidence: 77%
“…For c-closed graphs, we recently developed a kernel with O(c 7 k 8 ) vertices [22]. As for d-degenerate graphs, Kanj et al [18] and Erman et al [12] independently presented kernels of size k O(d) . Later, Cygan et al [5] provided a matching lower bound k o(d) on the kernel size.…”
Section: Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably the most important kernelization result in d-degenerate graphs is due to Philip et al [29] who showed a O(k (d+1) 2 ) size kernel for Dominating Set, and an O(k d+1 ) size kernel for Independent Dominating Set. Erman et al [14] and Kanj et al [24] independently gave a O(k d ) kernel for the Induced Matching problem, while Cygan et al [8] showed a O(k d+1 ) kernel is for Connected Vertex Cover. While all these results give polynomial kernels, the exponent of the polynomial depends on d, leaving open the question of kernels of polynomial size with a fixed constant degree.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by this, researchers seek for linear kernels with constants as small as possible. For example, by now there is known a 67k-vertex kernel for Dominating Set [3], a 28k-vertex kernel for Induced Matching [8] or a 75k-vertex kernel for Maximum Triangle Packing [17].…”
Section: Introductionmentioning
confidence: 99%